PROGRAM TO STRENGTHEN STUDENTS’ AL-QURAN LITERACY THROUGH MENTORING METHODS IN THE HIGHER EDUCATION ENVIRONMENT AT TELKOM UNIVERSITY - Hilmi, Fuad (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
The Quranic literacy strengthening program for university students is a strategic effort to improve Quranic reading and writing skills while simultaneously developing religious character in the university environment. This community service activity aims to improve students’ Quranic literacy skills through the implementation of a structured, intensive, and sustainable mentoring method. The mentoring method was chosen because it allows for direct assistance between mentors and students, making the learning process more effective, personalized, and tailored to the ability level of each participant. The program is implemented through several stages, namely identifying students’ initial abilities, forming mentoring groups, implementing routine Quranic reading and writing lessons, and periodically evaluating participants’ progress. The results of the activity show an increase in fluent Quranic reading skills, better accuracy of makhraj and tajwid, and increased student motivation in studying the Quran. In addition, this program also has an impact on the formation of positive habits in religious interactions on campus. The mentoring method has proven effective in improving Quranic literacy among university students. This program is expected to become a model for strengthening Quranic education that can be implemented sustainably in the academic environment.